Overexploitation, Recovery, and Warming of the Barents Sea Ecosystem During 1950–2013 - Pedersen, Torstein; Mikkelsen, Nina; Lindstrøm, Ulf; Renaud, Paul E.; Nascimento, Marcela C.; Blanchet, Marie-Anne; Ellingsen, Ingrid H.; Jørgensen, Lis L.; Blanchet, Hugues (Frontiers in Marine Science, 2021)
The Barents Sea (BS) is a high-latitude shelf ecosystem with important fisheries, high and historically variable harvesting pressure, and ongoing high variability in climatic conditions. To quantify carbon flow pathways and assess if changes in harvesting intensity and climate variability have affected the BS ecosystem, we modelled the ecosystem for the period 1950 to 2013 using a highly trophically-resolved mass-balanced food web model (Ecopath with Ecosim). Ecosim models were fitted to time series of biomasses and catches, and were forced by environmental variables and fisheries mortality. The effects of drivers, fishing mortality, primary production proxies related to open-water area and capelin-larvae mortality proxy, on ecosystem dynamics were evaluated. The ecosystem passed a phase of overexploitation with low biomasses of top-predator groups and some trophic cascade effects and increases in prey stocks during the period 1970-1990. Despite heavy exploitation of some groups, the basic ecosystem structure seems to have been preserved. After 1990, when the harvesting pressure was relaxed, most harvested groups showed recovery and increases in biomass, and the Ecosim model fitted the time-trends of most exploited boreal groups well. These biomass increases were accompanied by and likely driven by an increase in primary production as a result of a combination of warming and a decrease in ice-coverage. Some unexploited arctic groups decreased during the warm period after 1995 and the trends for these groups were not well predicted by the model. The Ecosim model successfully predicted the increasing trends in krill and jellyfish groups after 1995. The krill flow pathway was identified as especially important as it supplied both medium and high trophic level compartments, and this pathway was indicated to increase in importance during the warming after ca. 2000. The modelling results revealed complex interplay between fishery and variability of lower trophic level groups that differs between the boreal and arctic functional groups and has importance for ecosystem management.